The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s12028-010-9390-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular Fibrinolysis for Intracerebral Hemorrhage with Severe Ventricular Involvement

Abstract: Intraventricular hemorrhage (IVH) has been associated with poor prognosis in patients with spontaneous intracerebral hemorrhage. Several factors contribute to the deleterious effects of IVH, including direct mass effects of the ventricular blood clot on ependymal and subependymal brain structures, mechanical and inflammatory impairment of the Pacchioni granulations by blood and its breakdown products, and disturbance of physiological cerebrospinal fluid (CSF) circulation. Acute obstructive hydrocephalus repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
29
2
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 57 publications
4
29
2
8
Order By: Relevance
“…Several meta-analyses (on observational studies and small randomized trials) all suggested that intraventricular rtPA may be an effective strategy for reducing mortality and improving functional outcome, with the potential for decreasing permanent shunt rates without significant increase in complications. [19][20][21] Adverse events in this study were lower than the reported rates and support data showing that intraventricular fibrinolysis does not significantly increase the risk of rehemorrhage or infection. 21 The soonto-be-completed Phase III multinational, randomized controlled trial (Clot Lysis Evaluation of Accelerated Resolution of Intraventricular Hemorrhage [CLEAR-III]) of 500 patients with primary or secondary spontaneous IVH randomized to intraventricular fibrinolysis with rtPA or placebo should provide the highest quality evidence on the benefits and complications of this treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Several meta-analyses (on observational studies and small randomized trials) all suggested that intraventricular rtPA may be an effective strategy for reducing mortality and improving functional outcome, with the potential for decreasing permanent shunt rates without significant increase in complications. [19][20][21] Adverse events in this study were lower than the reported rates and support data showing that intraventricular fibrinolysis does not significantly increase the risk of rehemorrhage or infection. 21 The soonto-be-completed Phase III multinational, randomized controlled trial (Clot Lysis Evaluation of Accelerated Resolution of Intraventricular Hemorrhage [CLEAR-III]) of 500 patients with primary or secondary spontaneous IVH randomized to intraventricular fibrinolysis with rtPA or placebo should provide the highest quality evidence on the benefits and complications of this treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, IVF using rtPA has been mainly investigated and is currently being evaluated in smaller ICH (<30 mL in the ongoing multicenter phase III CLEAR-IVH trial). 11,12,19 Concerning secondary rebleeding, we could not find a significant difference between the IVF group and controls. Compared with the published results of the phases A and B of the CLEAR-IVH trial, 12 rebleeding was slightly less common in our study but comparable in the IVF group.…”
Section: Discussioncontrasting
confidence: 72%
“…10 Considering those pathomechanisms, there seems to be a clear rationale for the fast removal of blood and blood breakdown products from the ventricular system. Intraventricular fibrinolysis (IVF), that is, the administration of fibrinolytic agents as recombinant tissue plasminogen activator (rtPA) into the ventricles, seems to be an emerging and promising treatment strategy, 11 which is currently being investigated in a large phase III multicenter trial (Clot Lysis: Evaluating Accelerated Resolution of Intraventricular Hemorrhage [CLEAR-III]). 12,13 In the context of IVF, rtPA toxicity has been a source of concern because animal studies have shown that rtPA may exert dose-dependent proedematous and neurotoxic effects.…”
mentioning
confidence: 99%
“…Although the literature is consistent for IVH being a predictor of poor outcome in ICH, [10][11][12][13][14][15] there is uncertainty on the strength and pattern of association. One study suggests a curvilinear relationship between IVH volume and 30-day mortality, with 10 to 15 mL of IVH proposed as an appropriate threshold for predicting poor outcome in patients with comatose state (Glasgow Coma Scale scores <8), 5 whereas another study indicates IVH volumes >20 mL as being relevant for survival.…”
Section: Discussionmentioning
confidence: 99%